Microsatellite Instability in Adenomas as a Marker for Hereditary Nonpolyposis Colorectal Cancer - Loukola, Anu (American Society for Investigative Pathology, 1999)
Hereditary nonpolyposis colorectal cancer (HNPCC) is the most common of the well-defined colorectal cancer syndromes, accounting for at least 2% of the total colorectal cancer burden and carrying a greater than 80% lifetime risk of cancer. Significant reduction in cancer morbidity and mortality can be accomplished by appropriate clinical cancer screening of HNPCC patients with mutations in mismatch repair (MMR) genes. Thus, it is desirable to identify individuals who are mutation-positive. In individuals with cancer, mutation detection can be accomplished relatively efficiently by germline mutation analysis of individuals whose cancers show microsatellite instability (MSI). This study was designed to assess the feasibility of screening colorectal adenoma patients for HNPCC in the same manner. Among 378 adenoma patients, six (1.6%) had at least one MSI adenoma. Five out of the six patients (83%) had a germline MMR gene mutation. We conclude that MSI analysis is a useful method of prescreening colorectal adenoma patients for HNPCC.